The Existence of Washback Effect in the Formative Assessment of Reading Comprehension among Students with Different Personalities at SMP IT Daarut Tahfidz Demak - Maulidhawati, Rini; Januarius Mujianto; Suwandi Suwandi (English Education Journal, 2024)
The research aims to analyze the existence of the washback effect in the formative assessment of reading comprehension among students with different personalities at SMP IT Daarut Tahfidz Demak. The research subjects are teachers and eighth-grade students at SMP IT Daarut Tahfidz Demak. The researchers used a mixed-method design. The result showed that formative assessment was the aspect that helped introverted students succeed in the teaching and learning process. Introverts typically prefer solitude, often speaking less and thinking carefully before taking action. They enjoy working alone or with just a few people and usually need to be more socially active. Conversely, the second research question revealed that extroverted students are more adept at communicating in a second language despite potential inaccuracies in their output. These traits significantly impact their language learning processes, suggesting that extroverts tend to be more effective communicators. Third, the outcomes indicated a washback effect in the formative assessment of reading comprehension among introverted students. The positive washback improved three areas: teaching methods, material, and time allotment. Fourth, the results showed a washback effect in the formative assessment of reading comprehension among extroverted students. The positive washback enhanced teaching techniques, instructional materials, and time management. Furthermore, the washback effect helps students increase their reading comprehension scores. An improvement in the post-test scores demonstrated it. Lastly, the result showed no interaction between the washback effect in the formative assessment in reading comprehension among students with introverted and extroverted personalities.